Green chemistry in mineral processing: Chemical and physical methods to enhance the leaching of silver and the efficiency in cyanide consumption - Alarcón A. (2018)
The leaching of valuable metals from mineral ores is the basis of several extractive economies around the world, but the strategies employed often need to rely on dangerous compounds such as cyanides. Due to the complex nature of most ores, leaching processes are slow and have a low efficiency in noble metal extraction, which is usually improved by fine-milling the mineral. In this manuscript, we consider this strategy, demonstrating that it may increase the amount of silver leaching, but at the expense of a higher consumption of cyanide, which renders the process inefficient (only 2% of consumed cyanide is employed to complex silver). The increase in the yield of the desired product without the smarter use of dangerous compounds is shown as a paradigm of the need to insert green chemistry principles in industrial processes. We further present the result of two potential strategies for greener mineral processing: the use of ultrasound to eliminate passivating layers formed during the leaching process and the use of chemical pretreatments to eliminate possible sources of passivation. These strategies can increase the amount of silver extraction and simultaneously increase the efficiency in cyanide consumption. The convenience of these pretreatments in the framework of the green chemistry principles, as well as the challenges towards their implementation at industrial scale, is discussed.